Electrochemical sensor based on multi-walled carbon nanotubes and 4-(((4-mercaptophenyl)imino)methyl) benzene-1,2-diol for simultaneous determination of epinephrine in the presence of acetaminophen - Roghayyeh Aghaei; Mohammad Mazloum-Ardakani; Mohammad Abdollahi-Alibeik; Ali Moaddeli (Shiraz University of Medical Sciences, 2018)
A carbon paste electrode modiﬁed with 4-(((4-mercaptophenyl)imino)methyl)benzene-1,2-diol (MIB) and multi-walled carbon nanotubes MIB /CNT/CPE) was prepared for determination of epinefrine (EP) in the presence of acetaminophen (AC). Cyclic voltammetry, chronoamperometry and differential pulse voltammetry (DPV) techniques were used to investigate the modiﬁed electrode for the electrocatalytic oxidation of (EP) and (AC) in aqueous solutions. The separation of the oxidation peak potential for EP- AC was 200 mV. Under the optimum conditions, the calibration curve for EP was obtained in the range of 1.0 to 25.0 µM and 25.0 to 500.0 µM. The diffusion coefﬁcient for the oxidation of EP at the surface of modiﬁed electrode was calculated as 5.76×10-5 cm2s-1.